Perspective on High-Rate Alkaline Water Splitting - Kou, Tianyi; Wang, Shanwen; Li, Yat (ACS materials letters, 2021)
Alkaline water splitting (AWS) represents a sustainable technology for hydrogen gas generation. In comparison to proton exchange membrane water splitting, AWS is an economical approach because non-platinum-group metal-based materials can be used as catalysts and it avoids the usage of expensive proton exchange membranes. Despite the rapid development of cost-effective and intrinsically active catalysts that showed record-breaking performances at low current density (tens of mA cm–2), the cell efficiency of AWS at large current density (>400 mA cm–2) is still limited. In this Perspective, we aim to share our thoughts on the design of hydrogen evolution and oxygen evolution catalysts for high-rate AWS, the possible problems in catalyst’s performance evaluation, and the stability issues of catalysts.